Fit street revamping streets to encourage walking to Marikina Elementary School for the prevention of childhood obesity - Mendiola, Rhodora Ylissa N.; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The emergence of urbanization and technology led the decrease in physical activity of people and resulted to the rapid increase of obesity prevalence, especially for pre-school children in their developing years. Urbanization decreased the accessibility of walking and physical activity facilities that resulted to an obesogenic environment. Moreover, the developing technology affects the lifestyle of the people and increases the sedentary time leading to permanent sedentary behavior. In Marikina City, it is evident that urbanization is the main cause of childhood obesity in the city. Due to high vehicular traffic, lack of safe pedestrian facility, and obesogenic environment, children don't engage in physical activity like walking and exercise. Marikina Elementary School is identified to have high prevalence of childhood obesity among other schools. Obese kinder children and their parents tend to use motorized vehicle over walking, because of safety concerns and lack of pedestrian facilities in the area. Safety is the main concern of the parents for them to walk to school and they want to have a secured and comfortable neighborhood. With this, the study aims, to plan walking routes to school with safe and comfortable environment through applying the needs and preferences of the main users to streets capes and landscape features. This also aims to enhance the physical activity of the kinder obese children by identifying the ideal energy expenditure needed to control their weight. Through these findings, the study produced planning strategies and policies to apply in order to fight childhood obesity through urban development. The study also produced landscape designs with safe and comfortable streetscapes for the walking routes, as well as engaging play features that invites moderate to vigorous physical activities to the children.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Cities and towns -- Growth